Kerjasama Keamanan Kooperatif Indonesia-Australia dalam Menangani Penyelundupan Manusia (Cooperative Security Cooperation Between Indonesia-Australia in Addressing People Smuggling) - Hayana, Nurul; Bainus, Arry; Sudirman, Arfin (Jurnal Inspirasi, 2020)
The cooperation between Indonesia-Australia in addressing people smuggling is dramatically increased due to the gap between the need of immigrants to move from the country of origin and the complicated legal regulation to enter the country of destination for the sake of meeting the basic necessities of life. This article used descriptive qualitative method with the data obtained through literature studies. This article utilized several concepts in the study of International Relations such as people smuggling and cooperative security. The cooperative cooperation made by both countries were running well in the period 2010 to 2012, it is marked by the decrease in the number of illegal immigrants to Australia. In the period 2013 to mid-2014, the cooperation running stagnant marked by the unilateral policy by Australia named Operation Sovereign Borders. This policy caused Indonesia to stop various security cooperation related to people smuggling between them. In 2015, Indonesia and Australia re-established the cooperation on the framework of cooperative security with a more comprehensive procedure. However, this cooperation resulting residual problems for Indonesia which turned into the last country of destination with a significant increase of the number of illegal immigrants coming over, doubled compare to the previous years.